The crossing [compact disc, unabridged] : a novel - Connelly, Michael, 1956- (Connelly, Michael, 1956- Lincoln lawyer novel., 2015)
Coming out of retirement to help his defense attorney half-brother prove that a client has been framed for murder, Detective Harry Bosch secretly teams up with former partner Lucia Soto to investigate possible corruption inside the LAPD.